Regulatory Hierarchies Controlling Virulence Gene Expression in Shigella flexneri and Vibrio cholerae - Dorman, Matthew J.; Dorman, Charles J. (Frontiers in Microbiology, 2018)
Gram-negative enteropathogenic bacteria use a variety of strategies to cause disease in the human host and gene regulation in some form is typically a part of the strategy. This article will compare the toxin-based infection strategy used by the non-invasive pathogen Vibrio cholerae, the aetiological agent in human cholera, with the invasive approach used by Shigella flexneri, the cause of bacillary dysentery. Despite the differences in the mechanisms by which the two pathogens cause disease, they use environmentally-responsive regulatory hierarchies to control the expression of gene expression that have some features, and even some components, in common. The involvement of AraC-like transcription factors, the Integration Host Factor (IHF), the Factor for Inversion Stimulation (Fis), small regulatory RNAs, the RNA chaperone Hfq, horizontal gene transfer, variable DNA topology and the need to overcome the pervasive silencing of transcription by H-NS of horizontally acquired genes are all shared features. A comparison of the regulatory hierarchies in these two pathogens illustrates some striking cross-species similarities and differences among mechanisms coordinating virulence gene expression. S. flexneri, with its low infectious dose, appears to use a strategy that is centred on the individual bacterial cell, whereas V. cholerae, with a community-based, quorum-dependent approach and an infectious dose that is several orders of magnitude higher, seems to rely more on the actions of a bacterial collective